2020
DOI: 10.1111/jsr.13097
|View full text |Cite
|
Sign up to set email alerts
|

Psychological interventions to improve sleep in college students: A meta‐analysis of randomized controlled trials

Abstract: Summary Sleep disturbances and insomnia are common in college students, and reduce their quality of life and academic performance. The aim of this meta‐analysis was to evaluate the efficacy of psychological interventions aimed at improving sleep in college students. A meta‐analysis was conducted with 10 randomized controlled trials with passive control conditions (N = 2,408). The overall mean effect size (Hedges’ g) of all sleep‐related outcomes within each trial was moderate to large (g = 0.61; 95% confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 94 publications
2
19
1
Order By: Relevance
“…The present results are consistent with prior trials investigating psychological sleep interventions in domestic college students with a mean effect size of g = 0.61 (Saruhanjan et al, 2020), revealing similar effects of internet‐based interventions on the improvement of sleep difficulties (e.g. Freeman et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present results are consistent with prior trials investigating psychological sleep interventions in domestic college students with a mean effect size of g = 0.61 (Saruhanjan et al, 2020), revealing similar effects of internet‐based interventions on the improvement of sleep difficulties (e.g. Freeman et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…As part of the World Health Organisation (WHO) World Mental Health International College Student initiative (Cuijpers et al, 2019), internet‐based interventions as low‐threshold treatments are suggested to help overcome such barriers among college students (Ryan, Shochet, & Stallman, 2010), and to be a viable solution as prevention or early intervention (Buntrock et al, 2016; Sander, Rausch, & Baumeister, 2016). In fact, internet‐based interventions seem to effectively improve sleep difficulties among college students, comparable to face‐to‐face psychological interventions (Saruhanjan et al, 2020). Yet, studies investigating the efficacy of internet‐based sleep interventions for international college students are lacking, contrasting a well‐demonstrated efficacy of such interventions in clinical samples (Zachariae, Lyby, Ritterband, & O’Toole, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…"30 Data suggest that psychological interventions for improving sleep are efficacious among college students. 31…”
Section: College Health Educationmentioning
confidence: 99%
“…As suggested by Saruhanjan et al. (2021), young college students ‘ …face numerous new challenges, such as establishing identity and future life goals, reaching momentous life decisions, living independently, handling finances, managing academic demands, and modifying existing and adopting new social roles ’ (p. 2). Additionally, the potential for inconsistent wake–sleep timing due to more flexible weekday schedules and the increased lure of late‐night weekend socialising (Foulkes et al., 2019; Owens et al., 2017), combined with the lack of knowledge regarding sleep hygiene practices (Gellis et al., 2014), are likely to contribute to the high prevalence of insomnia observed in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Within the college student population, insomnia has been associated with lower GPA and poorer academic performance (Gaultney, 2010; Vedaa et al., 2019), depression (Akram et al., 2019) and higher health care utilisation (Bramoweth & Taylor, 2012). College can be a particularly stressful period for young adults, which may be a precipitating and maintaining factor in insomnia (Bastien et al., 2004; Saruhanjan et al., 2021). More than a quarter of undergraduates report high levels of stress, with problems ranging from academic demands, to work, to roommates, to the ill‐health or death of a loved one (American College Health Association, 2020).…”
Section: Introductionmentioning
confidence: 99%